Faktor-Faktor yang Berpengaruh terhadap Nilai Perusahaan dengan Return on Asset (ROA) sebagai Variabel Moderating (Studi Empiris pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di BEI Periode 2020-2024) - Al Fatihah, Reinka Ayu Imania; Badjuri, Achmad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Firm value reflects investors’ perception of a company’s performance and future prospects, serving as a positive signal of operational success. This study aims to examine the influence of dividend policy, leverage, and sales growth on firm value, with Return on Assets (ROA) acting as a moderating variable. The research focuses on consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A total of 100 observations were selected using purposive sampling. Data were analyzed using panel regression with SPSS. The findings indicate that: (1) dividend policy has a positive and significant effect on firm value; (2) leverage has a negative and significant effect; (3) sales growth has a negative but insignificant impact; (4) ROA strengthens the effect of dividend policy; (5) ROA weakens the effect of leverage; and (6) ROA also strengthens the influence of sales growth on firm value.